Kesesuaian Penulisan Resep Pasien BPJS Dengan Formulrium Nasional Di Poli Penyakit Dalam Rumah Sakit Islam Hasanah Mojokerto Periode Oktober – Desember 2021 - andri priyoherianto (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
Social security is a form of social protection that guarantees all Indonesian people to be able to meet the needs of a decent life. The Social Security Administration Agency (BPJS) is one of the institutions established to administer social security assistance programs in Indonesia. To overcome the imbalance between the contributions received from the community and the health costs incurred by BPJS, efforts are made to optimize BPJS patient prescribing based on the National Formulary as a reference. So that the hospital can control the quality and cost of treatment, and optimize services to patients. Research Methods: This research is a nonexperimental research that is descriptive in nature with retrospective data collection during the period October - December 2021, using the purposive sampling method, namely examining existing samples with certain considerations. The data are presented in tabular form and are described and calculated in percentage terms. A prescription is said to be in accordance with the National Formulary if all the drugs are included in the National Formulary. The results showed that the suitability of prescription writing with the National Formulary based on prescription sheets was 74.19% which was in accordance with the National Formulary and 25.81% which was not according to the National Formulary, while the conformity of prescription writing to the National Formulary based on drug items was 93.14% which was in accordance with the Formulary. National and 6.86% which is not in accordance with the National Formulary. Conclusion: The results of this study indicate that the recipes studied are not fully in accordance with the National Formulary.